Cas9‐guided haplotyping of three truncation variants in autosomal recessive disease. Issue 7 (28th April 2022) - Natsuga, Ken; Furuta, Yoshikazu; Takashima, Shota; Nohara, Takuma; Huang, Hsin‐Yu; Shinkuma, Satoru; Nakamura, Hideki; Katsuda, Yousuke; Higashi, Hideaki; Hsu, Chao‐Kai; Fukushima, Satoshi; Ujiie, Hideyuki
Abstract: An autosomal recessive disease is caused by biallelic loss‐of‐function mutations. However, when more than two disease‐causing variants are found in a patient's gene, it is challenging to determine which two of the variants are responsible for the disease phenotype. Here, to decipher the pathogenic variants by precise haplotyping, we applied nanopore Cas9‐targeted sequencing (nCATS) to three truncation COL7A1 variants detected in a patient with recessive dystrophic epidermolysis bullosa (EB). The distance between the most 5′ and 3′ variants was approximately 19 kb at the level of genomic DNA. nCATS successfully demonstrated that the most 5′ and 3′ variants were located in one allele while the variant in between was located in the other allele. Interestingly, the proband's mother, who was phenotypically intact, was heterozygous for the allele that harbored the two truncation variants, which could otherwise be misinterpreted as those of typical recessive dystrophic EB. Our study highlights the usefulness of nCATS as a tool to determine haplotypes of complicated genetic cases. Haplotyping of multiple variants in a gene can determine which variant should be therapeutically targeted when nucleotide‐specific gene therapy is applied. Abstract : Although rare, detecting three or more disease‐causing variants in a patient's gene can be puzzling. Nanopore Cas9‐targeted sequencing deciphers the pathogenic variants by precise haplotyping in such cases.